Artificial Intelligence and Educational Guidance: Towards a Smarter Future in Supporting Students - hanna, abdelkader (Journal of Social Sciences and Humanities, 2025)
This study aims to investigate how artificial intelligence (AI) is changing educational guidance by providing individualized, data-driven help that improves the academic and career choices of students. Using cutting-edge technology such as predictive analytics, natural language processing, and machine learning, artificial intelligence systems offer customized learning routes, early intervention identification of at-risk kids, and career options based on academic strengths and market trends. Virtual assistants driven by artificial intelligence improve accessibility and offer real-time assistance all around. Still, issues including algorithmic prejudice, data privacy concerns, and restricted access at underfunded institutions need careful thought. The study found that although artificial intelligence greatly increases the accuracy of suggestions and efficiency, differences in access and data security remain major problems. Diversity of training data, ethical norms, hybrid guiding models, and improved digital infrastructure are among the ideas for successful AI integration. In the end, artificial intelligence offers a chance to design a more inclusive, intelligent teaching tool set. Ensuring that artificial intelligence fairly serves every student depends on addressing the ethical and practical issues, therefore encouraging long-term educational and employment success.